The theoretical and methodological conception for the structuring of the ability to comprehensively treat pain in the General Physician training - José Julio Ojeda González; Miriam Iglesias León (Medisur)
Professional skills constitute a content dimension in the doctor's training model; They express the practical actions that must be acquired in the training model and, through them, it is possible to learn the demands that come with carrying out an adequate interrogation, a correct comprehensive physical examination and the application of the scientific method in the study of the health illness process in the individual, family and community. The aim of this work is to present the theoretical and methodological conception for structuring the ability to comprehensively treat pain in the General Physician’s training. An approach to its theoretical-methodological supports from Medical Education is presented, as the profession specific skill. Their training is conceived in the development of the teaching-educational-research process during the health-disease process and during education at work, supported by the logic of the clinical method as an indispensable premise for their training. The contents of different specialties that contribute to the treatment of pain in an integrated manner are required.